Wild camping and the weight of tourism. (September 2019) - Rantala, Outi; Varley, Peter
Wild camping forms a specific social reality within which tourists often claim not to be tourists and within which the capitalist practices central to tourism are messy. Yet, wild camping exemplifies the core idea in tourism: engaging in time during which time is 'free'. Here the concern is with the ways in which we 'do' going camping. We take material interaction with space, place and things as a starting point, via ethnomethodologically informed ethnography, in focusing upon the deployment of mundane, taken-for-granted assumptions, knowledge and practices. We find urban nomads engaged in the clearing, freedom and escape of the outdoors (the lightness), but anchored by the materialities of doing everyday life work, weighted with responsibilities towards nature, things and people.